Analysis of the relation between the golden ratio and the facial parameter - Melissa Andrea Díaz Salés; Luis Oscar Pacheco Fernández; Mariano Ortiz Pizarro; María Elizabeth Cruz Flores; Rosse Mary Falcón-Antenucci (Editorial Ciencias Médicas, 2018)
Introduction: the clinical ability to modify the dentofacial form through orthodontic treatment, maxillofacial surgery, or plastic surgery requires an understanding of facial beauty, including the evaluation of facial aesthetics, proportions, and symmetry. Objective: to analyze the relationship between the components of the golden ratio and the facial parameter of students in the province of Chiclayo. Methods: the study population was represented by 88 students who met the following inclusion criteria: age between 17 and 28 years, both sexes, without orthodontic treatment, with class I malocclusion and complete dentition. A data collection form for craniofacial anthropometric measurements was designed. The examiners were calibrated, the stability of the intra- and inter-rater concordance was evaluated using the Cohen's Kappa coefficient. For the contrast of the hypothesis, the correlation coefficient square chi was used. For all statistical tests, the level of significance was 5 % (p< 0.05). Results: 65.91 % of all the patients were observed to have a divine proportion in their external dimension: 48.86 % are brachifacial, 13.64 % mesofacial, and 3.41 % dolichofacial. 57.95 % of the total number of patients presented divine proportion in its vertical relation: 42.05 % are brachifacial, 10.23 % mesofacial, and 5.68 % dolichofacial. Regarding the harmonic profile, 70.45 % of the total number of patients did not present a divine proportion: 53.41 % are brachifacial, 10.23 % are mesofacial, and 6.82 % are dolichofacial. Conclusions: there is only a relationship between the golden ratio in its external dimension component and the facial parameter. The golden ratio was fulfilled in all its components, in a greater percentage in the brachifacial individuals, and there was a predominance of the golden ratio in the female sex.